Effect of pulmonary training for community‐dwelling frail older adults with chronic stroke: A randomized controlled pilot trial. (30th November 2021) - Maki, Naoki; Sakamoto, Harumi; Takata, Yu; Taniguchi, Keisuke; Wijesinghe, Ashoka; Okamura, Junko; Kawamura, Tomoyuki; Yanagihara, Takahiro; Saeki, Yusuke; Kitazawa, Shinsuke; Kobayashi, Naohiro; Kikuchi, Shinji; et al.
Abstract: Background: Decreased pulmonary function and poor deglutition are a major risk factor for poststroke aspiration pneumonia. We analyzed the benefits of pulmonary training on pulmonary function, deglutition, and quality of life (QOL) in community‐dwelling, frail elderly people with chronic stroke. Method: This study was designed as an open, randomized, controlled pilot trial. The participants, who were frail older adults with a history of stroke, were randomized to 2 rehabilitation groups: intervention group ( n  = 15) and control ( n  = 15). All participants (65–94 years) attended twelve 20‐min sessions twice a week for 6 weeks of either standard rehabilitation (control group) or standard rehabilitation with pulmonary training including home pulmonary exercise (intervention group). The main outcome measures were pulmonary function (%MIP), deglutition (DRACE), and QOL (SF8･PCS), while secondary outcomes were muscle strength (grip and abdominal), thorax flexibility, 6‐min walk distance, and activities in daily living. All outcomes were measured both prior to training and after the 12 sessions. Results: The intervention group showed significant improvement in %MIP (95% CI, 2.9–31.6; p  < 0.01), DRACE (95% CI, −4.1–0.1; p  < 0.01), and SF8･PCS (95% CI, 2.5–7.2; p  < 0.01) compared with controls. There were no cognitive function decline and higher brain dysfunction. Conclusions: These results suggest that the addition of pulmonary training including home pulmonary exercise to a standard rehabilitation program could improve pulmonary function, deglutition, and QOL in frail elderly people with chronic stroke. Abstract : This study suggest that the pulmonary training could improve pulmonary function, deglutition, and QOL in frail elderly people with chronic stroke.